Effectiveness of Alcoholic Beverage Regulation Enforcement for Public Order in Gorontalo City - Ahmad Hidayat Djabarudin; Zamroni Abdussamad; Julius T. Mandjo (Journal of Law, Human Rights, Immigration, and Corrections, 2026)
This article examines the effectiveness of Gorontalo City Regional Regulation Number 3 of 2017 on alcoholic beverage control and supervision in realizing public order. The study responds to the persistence of hidden and adaptive illegal sales despite the regulation’s administrative objectives. Using empirical legal research with a qualitative approach, data were collected through interviews with Civil Service Police Unit officers, community information, observation, and supporting documents, then analyzed through legal effectiveness and law enforcement theories. The findings show that implementation has occurred through patrols, raids, supervision, enforcement, and public complaint services. However, effectiveness remains moderate because violations persist, operational facilities are limited, public compliance is uneven, and legal culture has not fully supported social control. This article contributes an empirical assessment of regional regulation implementation by linking legal substance, enforcement capacity, community participation, and public order. Strengthening supervision, sanctions, documentation, and community reporting is required in Gorontalo City context.